2019
DOI: 10.21608/edj.2019.72564
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Idiopathic Osteosclerosis in The Jaws of The Egyptian Population Using Cone Beam Computed Tomography

Abstract: Purpose: Idiopathic osteosclerosis is a common radiopaque lesion without clear cause that affects the mandible and maxilla. This study was conducted to assess the prevalence of idiopathic osteosclerosis in the jaws among Egyptian population. Subjects and Methods: 1100 CBCT scans were used to assess the prevalence, gender and age distribution, location, and size of idiopathic osteosclerosis. Results: Idiopathic osteosclerosis was found in 16.7% of the cases with equal distribution in males and females patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
4

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
3
0
4
Order By: Relevance
“…15 Another study detected IO in 16.7% of CBCT scans of Egyptians. 16 Another study on panoramic radiographs found IO in 2.4% of patients in a Croatian subpopulation. 17 Ledesma-Montes et al found IO in 5.6% of the intraoral radiographs of a Mexican population.…”
Section: Discussionmentioning
confidence: 96%
“…15 Another study detected IO in 16.7% of CBCT scans of Egyptians. 16 Another study on panoramic radiographs found IO in 2.4% of patients in a Croatian subpopulation. 17 Ledesma-Montes et al found IO in 5.6% of the intraoral radiographs of a Mexican population.…”
Section: Discussionmentioning
confidence: 96%
“…Penelitian yang dilakukan oleh Zayet dan Hasan (2019) menunjukkan hasil bahwa persentase wanita dan laki-laki yang mengalami idiopathic osteosclerosis memiliki hasil yang hampir sama yaitu 16,6% pada wanita dan 16,9% pada laki-laki. 10 Hasil serupa juga ditemukan pada penelitian yang dilakukan oleh Misirlioglu dkk (2013), Sisman dkk (2011), dan Azizi dkk (2017) yang menunjukkan bahwa tidak terdapat perbedaan yang signifikan terkait insiden lesi idiopathic osteosclerosis antara wanita dan lakilaki. [7][8][9] Kasus lesi idiopathic osteosclerosis yang dilaporkan dialami oleh seorang wanita berusia 36 tahun.…”
Section: Discussionunclassified
“…Hal tersebut dikarenakan lesi idiopathic osteosclerosis bersifat asimptomatik sehingga lesi terlambat untuk terdeteksi. 10 Penelitian yang dilakukan oleh Ledesma-Montes dkk (2018) mendapatkan hasil bahwa idiopathic osteosclerosis dapat terjadi pada usia dekade pertama hingga ketiga. Ukuran lesi akan meningkat pada rentang usia 7-30 tahun dan akan menurun pada usia lebih lanjut.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…(a process of cell damage characterized by the rupture of the cell nucleus and the breakdown of chromatin). 10…”
Section: Formation Of Micronucleus and Cell Damaged Due To X-ray Radiationmentioning
confidence: 99%